2016
DOI: 10.2807/1560-7917.es.2016.21.37.30340
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus transmission: results from the integrated surveillance system in Italy, 2008 to 2015

Abstract: In Italy a national Plan for the surveillance of imported and autochthonous human vector-borne diseases (chikungunya, dengue, Zika virus disease and West Nile virus (WNV) disease) that integrates human and veterinary (animals and vectors) surveillance, is issued and revised annually according with the observed epidemiological changes. Here we describe results of the WNV integrated veterinary and human surveillance systems in Italy from 2008 to 2015. A real time data exchange protocol is in place between the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 20 publications
(21 reference statements)
4
94
1
Order By: Relevance
“…Moreover, all squirrels that showed VNT‐positive results for either WNV, USUV or TBEV were trapped in Piedmont. In this respect, our results contrast with the higher circulation of WNV and USUV detected in both humans and competent vectors in Lombardy region during the study period (Calzolari et al., ; CESME, ; Chiari et al., ; Mancini et al., ; Rizzo et al., ). The regional difference in seroprevalence observed in our study is likely related to habitat differences between the distribution range of grey squirrels in the two regions.…”
Section: Resultscontrasting
confidence: 95%
See 1 more Smart Citation
“…Moreover, all squirrels that showed VNT‐positive results for either WNV, USUV or TBEV were trapped in Piedmont. In this respect, our results contrast with the higher circulation of WNV and USUV detected in both humans and competent vectors in Lombardy region during the study period (Calzolari et al., ; CESME, ; Chiari et al., ; Mancini et al., ; Rizzo et al., ). The regional difference in seroprevalence observed in our study is likely related to habitat differences between the distribution range of grey squirrels in the two regions.…”
Section: Resultscontrasting
confidence: 95%
“…As surveillance programmes and early warning systems towards WNV, USUV and TBEV targeting human, animals and vectors have revealed recurrent circulation of these viruses in northern Italy (e.g., Rezza et al., ; Rizzo et al., ), the goal of this study was to determine the exposure to these flaviviruses in alien grey squirrel populations introduced in the area.…”
Section: Introductionmentioning
confidence: 99%
“…The first evidence of WNV was in horses in 1998; the virus re‐emerged in 2008 when human cases of neuroinvasive disease were observed . WNV lineage 1 was responsible for the human cases reported up to 2011, but since then, extensive circulation of WNV lineage 2 was demonstrated, and the strains were related either to the Hungarian or the Volgograd sublineages . Analysis of WNV genome sequences demonstrated that old WNV strains were no longer detected after having caused outbreaks, and appeared to be displaced by new strains.…”
Section: Mosquito‐transmitted Virusesmentioning
confidence: 99%
“… Reproduction of the images listed below is prohibited and permission must be sought directly from the copyright holder: Figure 1 and Figure 3 (Annex): © ICT – Istituto Zooprofilattico Sperimentale dell'Abruzzo e del Molise ‘G. Caporale’; Table 6: © World Organisation for Animal Health (OIE); Figures 1,2 (Annex): Rizzo et al., (CC BY 4.0). Eurosurveillance …”
mentioning
confidence: 99%
“…Figure 1 and Figure 3 (Annex): © ICT – Istituto Zooprofilattico Sperimentale dell'Abruzzo e del Molise ‘G. Caporale’; Table 6: © World Organisation for Animal Health (OIE); Figures 1,2 (Annex): Rizzo et al., (CC BY 4.0). Eurosurveillance…”
mentioning
confidence: 99%